Meeting the Alien An Introduction to Exosociology - Anton, Andreas; Schetsche, Michael (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer VS, 2023)
Is mankind alone in the universe? Will we ever encounter intelligent life beyond Earth? These questions have been asked for centuries. Recent advances in the fields of astrophysics, astronomy and astrobiology make it more likely than ever before, that Earth may not be the only inhabited planet, and that humanity may not the only intelligent species in the universe. What would be the consequences of contact with an extraterrestrial intelligence? This question is at the heart of the emerging discipline of exosociology. According to the authors, first contact with an extraterrestrial intelligence poses enormous risks for humanity. These risks come not only from extraterrestrials, but above all from ourselves. We should be prepared. Michael Schetsche and Andreas Anton's comprehensive introduction to exosociology was first published in German in 2019. The book has been widely acclaimed in Germany and internationally. It is now available in English for the first time. The contents - Humanity in the cosmos - The scientific search for extraterrestrial intelligences - Problems of communication and understanding - Terrestrial consequences of first contact - Proto-sociology of extraterrestrial civilizations - Hot potatoes of scientific alien research The target groups The book addresses everyone who wants to deal scientifically with the position of humans in the cosmos and with the question of the existence of intelligent extraterrestrial life. Authors Dr. Andreas Anton is a researcher at the Institute for Frontier Areas of Psychology and Mental Health (IGPP) in Freiburg, Germany, and teaches at the Institute for Sociology at the University of Freiburg. Dr. Michael Schetsche teaches as an extraordinary professor at the Institute of Sociology at the University of Freiburg.
The aliens at the gates of sociology -- Thinking about aliens -- The earth in space -- SETI - History, methods and presuppositions of the scientific search for extraterrestrial intelligences -- SETA - The search for extraterrestrial artifacts -- Calls in the dark forest - risky communication attempts -- Methodological considerations for the scenario analysis of first contact -- Consequences of first contact - A scenario analysis -- The cultural preparation for the first contact -- Proto-Sociology of extraterrestrial civilizations -- Hot potato in scientific alien research -- Outlook.
Keywords: Culture; Sociology; Social sciences -- Philosophy; Sociology of Culture; Sociological Theory; Social Theory